SINTESIS METIL ESTER NITRAT DARI MINYAK BIJI NYAMPLUNG (CALOPHYLLUM INOPHYLLUM L) - Astam, Amal; Nurliana, Laily; Kadidae, La Ode (IKIP Mataram, 2019)
Research on the synthesis of methyl ester nitrate from nyamplung seed oil (Calophyllum inophyllum L.). The aims of study are to are to determine the nitrate methyl ester can be synthesized from nyamplung seed oil determine the yield of the transesterification and nitration reaction from nyamplung seed oil. In this study nyamplung seed oil was obtained from pressing nyamplung seeds using a hydraulic press, then the crude oil obtained was subsequently degumming to remove gum. Free oil of the etherified gum then transesterification with methanol. The transesterification results are then titrated and produce nitric methyl esters. Characterization of nitric methyl ester by spectrophotometer IR shows functional groups C-ONO2, C=C dan C-NO2 at wave number 1635,64 cm-1 1550,77 cm-1 dan 1365, 60 cm-1. The yield of transesterification of nyamplung oil was 64.66% and the nitration yield was 10.6%.